(Re)membering in improvisation as anticolonial ruptures: (un)doing literacy work in puerto rico. (2nd January 2023) - Liliana Medina, Carmen; del Rocío Costa, Maria
ABSTRACT: Grounded in 10 years of critical literacy work in Puerto Rico, the authors engage readers creatively, to share key events in both our experiences as local teachers and as theatre activists in Puerto Rico. Our long-term purpose has been to explore new creative approaches to doing educational research and pedagogies that rupture traditional colonial structures of doing literacy work in local classrooms. After we share these creative stories we explore the idea of improvisation as Anticolonial literacy (un)doings to disrupt colonial imposed ways of inhabiting classroom spaces.